Pengembangan Platform Cerita Digital Interaktif Menggunakan Decoupled Architecture React Laravel - Luthfiyana Mahrurin Abadi; Rizky Parlika (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Children's literacy can be improved through interactive learning media. A digital children's story platform, previously a mobile application, required web version development to expand user accessibility via browsers. The main challenge in this development was presenting multimedia content such as text, images, and audio dubbing synchronously scene-by-scene without degrading system performance, as well as facilitating reader interaction through a rating feature. This research aims to design and develop the platform using a Decoupled Architecture approach. The software development method used is Waterfall, encompassing requirement analysis, system design (UML, CDM, and PDM), implementation, testing, and maintenance. During implementation, ReactJS is utilized on the client-side for responsive interface rendering and state management, while Laravel is implemented on the server-side as a RESTful API provider to manage multimedia asset transmission, rating records, and the MySQL database. Functional system testing was evaluated using Black-box Testing, while user experience was validated using Spearman's Rank Correlation. The results indicate that this architectural separation (front-end and back-end) effectively resolves server overload issues commonly found in monolithic architectures and produces a seamless, stable asynchronous data transmission system across various devices.